Induction chemotherapy in locally advanced squamous cell carcinoma of the head and neck. (9th December 2020) - Okano, Susumu; Homma, Akihiro; Kiyota, Naomi; Tahara, Makoto; Hanai, Nobuhiro; Asakage, Takahiro; Matsuura, Kazuto; Ogawa, Takenori; Saito, Yuki; Sano, Daisuke; Kodaira, Takeshi; Motegi, Atsushi; et al.
Abstract: In order to maximize the benefit of induction chemotherapy, practice based on a comprehensive interpretation of a large number of clinical trials, as in this review, is essential. The standard treatment for locally advanced squamous cell carcinoma of the head and neck is surgery or chemoradiation. However, induction chemotherapy followed by (chemo) radiotherapy may be used in some circumstances. Although many clinical trials of induction chemotherapy have been conducted, a rationale other than to preserve the larynx is still controversial. Selection of this modality should therefore be made with care. The current standard regimen for induction chemotherapy is docetaxel, cisplatin and 5-FU, but concerns remain about toxicity, cost and the duration of treatment. Regarding treatment after induction chemotherapy, it is also unclear whether radiation alone or chemoradiation is the better option. Furthermore, there is no answer as to what drugs should be used in combination with radiation therapy after induction chemotherapy. Several new induction chemotherapy treatment developments are currently underway, and future developments are expected. This review article summarizes the current position of induction chemotherapy for head and neck squamous cell carcinoma, based on the evidence produced to date, and discusses the future prospects for this treatment. Abstract : Induction chemotherapy is one of the organ preservation strategies for laryngeal and hypopharyngeal cancers, but its role for unresectable locally advanced squamous cell carcinoma of the head and neck is controversial.